The Modified Socket Shield Technique. Issue 8 (November 2018) - Han, Chang-Hun; Park, Kwang-Bum; Mangano, Francesco Guido
Abstract : Objective: In the anterior regions, the resorption of the buccal bone after tooth extraction leads to a contraction of the overlying soft tissues, resulting in an esthetic problem, particularly with immediate implant placement. In the socket shield technique, the buccal root section of the tooth is maintained, to preserve the buccal bone for immediate implant placement. The aim of this prospective study was to investigate the survival, stability, and complication rates of implants placed using a "modified" socket shield technique. Methods: Over a 2-year period, all patients referred to a dental clinic for treatment with oral implants were considered for inclusion in this study. Inclusion criteria were healthy adult patients who presented nonrestorable single teeth with intact buccal periodontal tissues in the anterior regions of both jaws. Exclusion criteria were teeth with present/past periodontal disease, vertical root fractures on the buccal aspect, horizontal fractures below bone level, and external/internal resorptions. The buccal portion of the root was retained to prevent the resorption of the buccal bone; the shield was 1.5 mm thick with the most coronal portion at the bone crest level. All patients then underwent immediate implants. In the patient with a gap between the implant and shield, no graft material was placed. All implants were immediately restored with single crowns and followed for 1 year. The main outcomes were implant survival, stability, and complications. Results: Thirty patients (15 males, 15 females; mean age was 48.2 ± 15.0 years) were enrolled in the study and installed with 40 immediate implants. After 1 year, all implants were functioning, for a survival rate of 100%; excellent implant stability was reported (mean implant stability quotient at placement: 72.9 ± 5.9; after 1 year: 74.6 ± 2.7). No biologic complications were reported, and the incidence of prosthetic complications was low (2.5%). Conclusions: The "modified" socket shield technique seems to be a successful procedure when combined with immediate implant placement, because the root fragment does not interfere with osseointegration and may be beneficial for the esthetics, protecting the buccal bone from resorption.